Mango Pectic Oligosaccharides: A Novel Prebiotic for Functional Food - Wongkaew, Malaiporn; Tangjaidee, Pipat; Leksawasdi, Noppol; Jantanasakulwong, Kittisak; Rachtanapun, Pornchai; Seesuriyachan, Phisit; Phimolsiripol, Yuthana; Chaiyaso, Thanongsak; Ruksiriwanich, Warintorn; Jantrawut, Pensak; Sommano, Sarana Rose (Frontiers in Nutrition, 2022)
Prebiotics are functional food ingredients that assist probiotic growth and render many other health benefits. Mango peel is the biomass of the processing industry and has recently been value-added as a dietary fiber pectin. Besides its general use as a food additive, mango peel pectin (MPP) is partially hydrolyzed by pectinase to obtain pectic oligosaccharides (POSs) that have recently gained attention as novel prebiotic products and in medical research. This review describes probiotic candidates responsible for the digestion of pectin derivatives and the advantages of POSs as functional additives and their current best retrieval options. Mango pectic oligosaccharide (MPOS) recovery from low methoxyl MPP from mango with prebiotic performance both in vivo and in vitro environments is discussed. Current research gaps and potential developments in the field are also explored. The overall worthiness of this article is the potential use of the cheap-green food processing bioresource for high-value components.